Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic - Skinner, Luís Felipe; Rocha, Rosana M.; Counts, Bailey K. (Zootaxa, 2019)
The genus Pyura is widely distributed with 99 valid species. Since 1961, Pyura vittata (Stimpson, 1852) has been reported to the Southwest Atlantic but new collections and a revision of the morphological characters of samples deposited in scientific collections revealed that samples had been confused with two other species: Pyura gangelion (Savigny, 1816) and Pyura beta sp. nov. present in the Caribbean sea and Brazil. In Brazil, P. vittata is not present south to Bahia, P. beta was found from Espírito Santo to São Paulo, while P. gangelion was only found in Espírito Santo, and we suggest that populations of both P. beta and P. gangelion are non-native in Brazil.